Budget impact of maternal vaccination with RSVpreF to protect privately insured infants in Dubai against respiratory syncytial virus - Mostafa Zayed; Jean Joury; Mohamed Farghaly; Sara Al Dallal; Ramya Mahendiran; Amy W. Law; Diana Mendes; Erin Quinn; Emily Kutrieb; Ahuva Averin (Human Vaccines & Immunotherapeutics)
Respiratory syncytial virus (RSV) manifesting as lower respiratory tract illness (LRTI; RSV-LRTI) represents a significant healthcare burden among infants in Dubai and worldwide. The novel bivalent stabilized prefusion F subunit vaccine (RSVpreF) for administration among pregnant women to protect infants against RSV-LRTI has been evaluated and approved for use in Dubai. We assessed the budget impact of year-round maternal RSVpreF use to prevent RSV-LRTI among privately insured non-Emirati infants living in Dubai. A deterministic cohort model was built to illustrate clinical and economic outcomes of RSV-LRTI among infants from birth to age 1 year for five annual birth cohorts. Model population comprised infants born to non-Emirati pregnant women; parameter values were estimated principally based on published sources using Dubai-specific data to the extent possible. Model outcomes included cases of disease (hospital, emergency department, outpatient clinic), disease-attributable deaths, and costs of disease and vaccination (in US$). Budget impact was reported in terms of overall cost and per-member per-year (PMPY) cost. With no intervention, there would be 23,267 RSV-LRTI cases (1,960 hospital; 5,655 emergency department 15,652 outpatient) and medical costs would total $11.5 M over 5 years. Targeting 10% of pregnant women with RSVpreF would prevent 855 cases and reduce infant medical care costs by $0.5 M. With vaccination costs estimated at $3.6 M, overall costs would increase by $3.1 M overall and $0.19 PMPY. Findings suggest that RSVpreF use among pregnant women would substantially reduce the clinical and economic burden of RSV-LRTI in infants, requiring an investment of just $0.19 PMPY by private health insurers.